2021
DOI: 10.1109/access.2021.3085835
|View full text |Cite
|
Sign up to set email alerts
|

Deep Face Age Progression: A Survey

Abstract: Face Age Progression (FAP) refers to synthesizing face images while simulating ageing effects, thus enabling predicting the future appearance of an individual. The generation of age-progressed face images brings benefits for various applications, ranging from face recognition systems to forensic investigations and digital entertainment. In particular, the recent success achieved with deep generative networks significantly leveraged the quality of age-synthesized face images in terms of visual fidelity, ageing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…GAN-based architectures have not only proven their worth in generating synthetic images but also in performing face-age progression (FAP). Grimmer et al (2021) have recently provided a comprehensive survey of deep face age progression, noting that GANs indeed produce remarkable face ageing results (cf. Figure 1).…”
Section: Face-age Progressionmentioning
confidence: 99%
“…GAN-based architectures have not only proven their worth in generating synthetic images but also in performing face-age progression (FAP). Grimmer et al (2021) have recently provided a comprehensive survey of deep face age progression, noting that GANs indeed produce remarkable face ageing results (cf. Figure 1).…”
Section: Face-age Progressionmentioning
confidence: 99%
“…In this section, we introduce the existing face aging methods that are more relevant to our approach, while a comprehensive review of face aging works can be found in [12], [13].…”
Section: Related Workmentioning
confidence: 99%
“…Thereafter, the resulting latent code can be shifted in the latent space, whereby the inverted image of the shifted vector results in an alteration of the original image. The technique can, for instance, be used for face age progression [13]. In addition to the face, some research have also been conducted for other biometric modalities, e.g.…”
Section: A Synthetic Data Generation For Face Analysismentioning
confidence: 99%